Pengembangan Kemampuan Multiple Intelligences Mahasiswa Perguruan Tinggi Keagamaan Islam melalui Organisasi Kemahasiswaan Intrakampus - Yahya, Fata Asyrofi; Diantoro, Fery (MUSLIM HERITAGE, 2023)
AbstractThis research departs from the empirical problem that undergraduate graduates contribute to the high number of unemployed in Indonesia. Among the causes is that the curriculum in higher education is more oriented towards achieving academic achievement. This research aims to explain the management of intracampus student organization activity programs in developing students' multiple intelligences abilities and measure the success of intracampus organizations in developing students' multiple intelligences abilities at IAIN Ponorogo. The research method uses a phenomenological approach and the type of research is qualitative. Data collection was carried out by observation, interviews and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results of this research include: first, management of the multiple intelligences capability improvement program through the stages of planning, organizing, implementing and monitoring. Program planning is carried out at the beginning of the year through work meetings taking into account the results of the previous period's activity evaluation. Organization is carried out by delegating tasks and responsibilities to each division to prepare and carry out UKM activity programs in developing students' multiple intelligences. At the program implementation stage, the chairman moves the field coordinator, then down to the management and down to the members. Program supervision is carried out by the head of UKM and the supervisor of each UKM to ensure that all program activities run according to plan. Second, the UKMs that succeeded in achieving 85% of their members' activity were UKM Self-Defense and UKM Mapala Post. Then those who succeeded in changing the abilities of their members by 80% included UKM PSRM, UKM SEIYA, UKM UKI, UKM Martial Arts, UKM Sports, UKM LPM Al-Millah, and UKM KSR. Meanwhile, those who managed to get achievements in the competition for approximately three years were all UKM except UKM LPM Al-Millah, UKM Kopma, and UKM Bahasa.AbstrakPenelitian ini berangkat dari problem empiris bahwa lulusan sarjana menyumbang jumlah pengangguran yang tinggi di Indonesia. Diantara penyebabnya yaitu kurikulum di perguruan tinggi lebih berorientasi dalam pencapaian prestasi akademik. Penelitian ini bertujuan untuk menjelaskan pengelolaan program kegiatan organisasi kemahasiswaan intrakampus dalam mengembangkan kemampuan multiple intelligences mahasiswa dan mengukur keberhasilan organisasi intrakampus dalam mengembangkan kemampuan multiple intelligences mahasiswa di IAIN Ponorogo. Metode penelitiannya menggunakan pendekatan fenomenologi dan jenis penilitiannya kualitatif. Pengumpulan data dilakukan dengan observasi, wawancara, dan dokumentasi. Teknik analisis datanya meliputi pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian ini diantaranya: pertama, pengeloaan program peningkatan kemampuan multiple intelligences melalui tahapan perencanaan, pengorganisasian, pelaksanaan, dan pengawasan. Perencanaan program dilakukan di awal tahun melalui rapat kerja dengan mempertimbangkan hasil evaluasi kegiatan periode sebelumnya. Pengorganisasian dilakukan dengan mendelegasikan tugas dan tanggung jawab kepada setiap devisi untuk menyusun dan menjalankan program kegiatan UKM dalam pengembangan multiple intelligences mahasiswa. Pada tahap pelaksanaan program, ketua menggerakkan koordinator bidang, kemudian turun ke pengurus dan turun sampai ke anggota. Pengawasan program dilakukan oleh ketua UKM dan pembina setiap UKM untuk memastikan semua program kegiatan berjalan sesuai perencanaan. Kedua, UKM yang berhasil mencapai 85% menjaga keaktifan anggotanya adalah UKM Bela Diri dan UKM Mapala Pasca. Kemudian yang berhasil mengubah kemampuan anggotanya sebesar 80% diantaranya adalah UKM PSRM, UKM SEIYA, UKM UKI, UKM Bela Diri, UKM Olahraga, UKM LPM Al-Millah, dan UKM KSR. Sedangkan yang berhasil mendapatkan prestasi dalam kompetisi perlombaan selama kurang lebih tiga ini adalah semua UKM kecuali UKM LPM Al-Millah, UKM Kopma, dan UKM Bahasa.